Vplyv počítačovej navigácie na dlhodobé výsledky po implantáciách totálnych endoprotéz kolenného kĺbu vykonaných menej skúseným operatérom - Lacko, Marek; Schreierová, D; Čellár, Róbert; Vaško, Gabriel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2018)
PURPOSE OF THE STUDY The study aims to evaluate the long-term results of computer-navigated total knee arthroplasties performed by less experienced surgeon performing a small number of procedures per year. MATERIAL AND METHODS In the prospective randomised study functional and radiological results, rate of revision and probability of clinical and radiological survival were compared in 30 computer-navigated (in 28 patients: 19 women, 9 men, with the mean age of 66.9 years) and 31 conventionally implanted (in 30 patients: 27 women, 3 men, with the mean age of 66.5 years) cemented total knee replacements without patellar resurfacing. The group was composed of patients who underwent surgery performed by the same surgeon who at the time of enrolment of patient in the study had no previous experience with the total knee replacement surgery and performed up to 30 such procedures annually. The mean follow-up of patients was 11 years. RESULTS No statistically significant differences were detected regarding the mean age, sex, body mass index and etiology of osteoarthritis of the operated knee. The mean duration of computer-navigated surgeries (101±14.1; 80-140 min) was considerably longer than the duration of conventional joint replacements (94±8.2; 80-100 min; p = 0.01). When evaluating the radiological results, a statistically significant difference was found between the groups only with respect to the mean value of dorsal inclination of the tibial component (88.2˚±2.1 vs 86.2˚±3, p = 0.02). The mean values of other monitored angles did not show any significant differences. The number of correct implants (with a deviation of 3 degrees from the target values) was statistically significantly higher in the group of computer-navigated joint replacement surgeries in all the monitored parameters (aFT: 87% vs. 67%, p = 0.04; α: 87% vs. 71%, p = 0.04; β: 87% vs. 65%, p = 0.03; γ: 93% vs. 74%, p = 0.02; δ: 90% vs. 77%, p = 0.04). Radiologic signs of unstable fixation were detected in 2 cases of computer-navigated joint replacement surgeries and in 7 cases of conventional replacements. Cumulative probability of radiologic survival at 10 years reached 93% in the compute-navigated surgery and 77.4% (p = 0.047) in the group with conventional procedure. In total, 4 revision surgeries with a reimplantation of at least one prosthetic component were reported. All the cases came from the conventional implantation group due to aseptic loosening of the endoprosthesis. In the computer-navigated group, one revision was performed for patellar pain, without replacing or adding any endoprosthetic component. The probability of clinical survival in computer-navigated replacements after 10 years was 100%, in conventional total knee replacements it was 87% (p = 0.04). The cumulative total endoprosthesis revision rate in the computer-navigated group was 3.3%, whereas in the group with conventional total knee replacements it was 12.9% (p = 0.04). The clinical assessment based on the WOMAC and Knee Society Scores showed no statistically significant differences. DISCUSSION The most common cause of the failure of total knee arthroplasties is the malposition of implants which results in early aseptic loosening. The radiologically correct position of knee endoprosthesis is seen in 80% of standard replacement surgeries performed by experienced surgeons. The potential error rate can even increase if the arthroplasties are performed by less experienced orthopaedic surgeons. The computer-navigated total knee replacement was introduced to make the position of implants more accurate. However, the question remains unanswered if more accurate positioning of the implants achieved with computer navigation decrease the revision rate and extend the long-term survival of knee endoprostheses. CONCLUSIONS Kinematic computer navigation allowed a less experienced and low-volume orthopaedic surgeon to make the implantation of endoprostheses more accurate, to decrease the total revision rate, and thus to ensure a higher probability of long-term survival of total knee arthroplasties. Key words:computer navigation, total replacement, knee joint, long-term outcomes, low-volume surgeon, less experienced surgeon.
Keywords: Long Term Adverse Effects; Arthroplasty, Replacement, Knee; Humans; Surgery, Computer-Assisted; chirurgie s pomocí počítače; lidé; osteoartróza; klinické kompetence; Prosthesis Failure; hodnocení výsledků zdravotní péče; Female; Male; selhání protézy; Osteoarthritis; Knee Prosthesis; totální endoprotéza kolene; Clinical Competence; senioři; protézy kolene; Aged; Outcome Assessment, Health Care; ženské pohlaví; mužské pohlaví; dlouhodobé vedlejší účinky